Mechanical properties of asbestos and basalt stone waste as structural concrete - Ni Putu Indira Saraswati Kumari Wisuryha; Putu Cinthya Pratiwi Kardita; Ida Ayu Made Dwitya Widani Manuaba; I Dewa Gede Byantara Nugraha; Abbror Ragil Putrawan (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
The Earth's average surface temperature has increased immensely, reaching 1.45 +/- 0.12 Celsius in 2023. This is linked to growing carbon emissions from industrial activities, particularly the construction sector. The production of 1 m3 of conventional concrete can emit up to 277.82 kg CO2. Indonesia remains the second-largest asbestos importer, contributing over 100,000 tons annually to the local construction sector in 2023. Most of the waste is unmanaged and causes health concerns. Simultaneously, Bali’s stone carving industry generates approximately 30% basalt stone waste, much of which remains unprocessed and is discarded into rivers or roadside drains. Nationally, Indonesia holds over 1 billion tons of basalt reserves, yet utilization remains low. Addressing these dual environmental issues, this study proposes a sustainable concrete innovation that utilizes 3% asbestos waste as a substitute for cement and 20% basalt waste as a replacement for coarse aggregate. The proposed concrete mix was tested following SNI 03-2847-2002, ASTM C39, and SNI 03-1974-1990. The results show a compressive strength of 44.26 MPa, higher than the required 41.4 MPa for high-strength concrete based on SNI 03-6468-2000. The modified mixture also has a 16.71 percent lower density than normal concrete and a slump value of 157.67 mm, indicating good workability. Furthermore, the mix reduces carbon emissions by 31.273 kg CO2 per m3 and lowers production cost by 43.9 percent, saving IDR 731,401 compared to conventional concrete with similar strength. These innovations show that asbestos and basalt waste can be transformed into low-carbon structural materials, promoting the circular economy while mitigating environmental risks from unmanaged industrial waste.